Ambrisentan for the treatment of pulmonary arterial hypertension: a budget impact analysis in the Italian context. (October 2014) - Barbieri, Marco; Zamboni, William; Pippo, Lara; Madaan, Prateek; Campana, Carlo
<x xml:space="preserve">Abstract</x> Introduction: Pulmonary arterial hypertension (PAH) is a rare disease involving small pulmonary arteries and is characterized by vascular proliferation and remodeling. The financial impact of therapies for the treatment of PAH in the Italian context is unknown. Objective: The objective of this study was to carry out a budget impact analysis comparing ambrisentan with bosentan for patients with class II or III PAH in the Italian context over a 3-year timeline. Methods: Data on efficacy and rate of treatment discontinuation were taken from two separate double-blind studies (no head-to-head studies were available) and supported by expert's opinion. The analysis was conducted from the perspective of the National Health System and included drug acquisition cost, direct medical costs associated to ambrisentan or bosentan treatment, and direct medical costs associated to the treatment of adverse events. Results: Over a 3-year timeline, total costs for the cohort of patients considered would be €86, 482, 146 with ambrisentan and €87, 594, 291 with bosentan. The sensitivity analysis corroborated the base case findings. Conclusion: According to the model results, it can be concluded that the use of ambrisentan instead of bosentan for eligible patients might lead to savings of about €1.1 million over a 3-year time horizon in Italy.